ANALISIS STRUKTUR RETORIKA DAN PENANDA KEBAHASAAN BAGIAN HASIL DAN PEMBAHASAN ARTIKEL JURNAL PENELITIAN BISA FKIP UNIB UNTUK BIDANG PENGAJARAN BAHASA - Yanita, Herni (UNIB Press, 2016)
This study aimed to describe macro rhetoric structures and linguistic markers in the result and discussion of BISA journal of language pedagogy. This study used descriptive method. The data in this research were linguistic markers in text from Research Articles (RA) entitled research journal article BISA that specifically discuss about language pedagogy. The analysis of rhetoric structure used Swales theory consisting of 8 moves. Meanwhile, linguistic markers were defined as text genre regarding to active and passive sentence and cohession markers. The analysis result of rhetoric structures from result and discussion session in research journal article BISA research articles were the movements that were used in the rhetoric structure of research journal article BISA Journal which were move 1 with (information about the research), move 2 (statement about the result of research), move 5 (explanation about the result of the research). On the other side, for the linguistic markers found in the result and discussion section of research journal articles BISA journal were: linguistic markers in all movements (1) active sentence and passive sentence (2) cohession markers.